Chromium (VI) Removal from Wastewater by Electrocoagulation Process Using Taguchi Method: Batch Experiments - Al-Nuaimi, Amenah S.; Pak, Kamal S. (Iraqi Journal of Chemical and Petroleum Engineering, 2016)
Electrocoagulation is an electrochemical method for treatment of different types of wastewater whereby sacrificial anodes corrode to release active coagulant (usually aluminium or iron cations) into solution, while simultaneous evolution of hydrogen at the cathode allows for pollutant removal by flotation or settling. The Taguchi method was applied as an experimental design and to determine the best conditions for chromium (VI) removal from wastewater. Various parameters in a batch stirred tank by iron metal electrodes: pH, initial chromium concentration, current density, distance between electrodes and KCl concentration were investigated, and the results have been analyzed using signal-to-noise (S/N) ratio. It was found that the removal efficiency of chromium increased with increasing current density and KCl concentration, and decreases with increasing initial chromium concentration and distance between electrodes, while pH shows peak performance curve. Experimental work have been performed for synthetic solutions and real industrial effluent. The results showed that the removal efficiency of synthetic solution is higher than industrial wastewater, the maximum removal for prepared solution is 91.72 %, while it was 73.54 % for industrial wastewater for the same conditions.